Climate change and industrial policy - Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper explores the implications of climate change for industrial policy (IP). Five implications are discussed, namely the need for international coordination of IPs; for putting human development, and not emission targets, as the overriding objective of low-carbon IP; of stimulating innovation for energy efficiency, energy diversification, and carbon capture and storage; and for aligning IP with trade policies. Finally the funding needs of low-carbon IPs are discussed, and the importance of private sector funding emphasized.
Keywords: L60; O25; Q54; Q55; 330; climate change; sustainable development; industrialization; industrial policy; low-carbon growth